2014
DOI: 10.1152/ajpcell.00284.2013
|View full text |Cite
|
Sign up to set email alerts
|

ALX/FPR2 receptor for RvD1 is expressed and functional in salivary glands

Abstract: Nelson JW, Leigh NJ, Mellas RE, McCall AD, Aguirre A, Baker OJ. ALX/FPR2 receptor for RvD1 is expressed and functional in salivary glands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 47 publications
3
56
0
Order By: Relevance
“…Besides its expression in immune cells such as macrophages and neutrophils, FPR2/ALX receptors have been found in epithelial cells, endothelial cells, microglia, salivary glands, cornea, spleen, lung and vascular smooth muscle (Bonnans et al, 2007;Chiang et al, 2006;Levy et al, 2002;Migeotte et al, 2006;Nelson et al, 2014;Wilson et al, 2008). In the present report it is shown that FPR2/ALX receptor is constitutively expressed in VSMC and that LPS increased its expression in both the cell line A7r5 and mouse aorta.…”
Section: Discussionsupporting
confidence: 58%
“…Besides its expression in immune cells such as macrophages and neutrophils, FPR2/ALX receptors have been found in epithelial cells, endothelial cells, microglia, salivary glands, cornea, spleen, lung and vascular smooth muscle (Bonnans et al, 2007;Chiang et al, 2006;Levy et al, 2002;Migeotte et al, 2006;Nelson et al, 2014;Wilson et al, 2008). In the present report it is shown that FPR2/ALX receptor is constitutively expressed in VSMC and that LPS increased its expression in both the cell line A7r5 and mouse aorta.…”
Section: Discussionsupporting
confidence: 58%
“…Other authors showed that the formyl peptide receptor 2 (Fpr2), which we found significantly upregulated in our microarrays (Table 1), is expressed in acinar cells of mouse SMG (38). This receptor promotes intracellular calcium responses 8.…”
Section: Discussionmentioning
confidence: 54%
“…and phosphorylation of ERK1/2 and Akt proteins which are associated with cell survival pathways (38). In addition, resolvin D1 (RvD1), which is a short-lived bioactive lipid produced during termination of inflammation and also a ligand for Fpr2, elicits anti-inflammatory and proresolving actions to prevent cell damage and promote tissue repair during the resolution of an inflammatory process (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…70 Resolvins also interacted with cytokines by blocking TNF-a-mediated effects in salivary gland tissue. 71 Importantly, the regulation of pro-resolving mediators appear to be influenced by neuronal functioning and may be reduced after neuronal injury and dysfunction associated with a reduction in Netrin-1 affecting resolvin D1 production. 72 Figure 3 (a) Normal nociceptor response to a noxious stimulus is shown.…”
Section: Peripheral Sensitizationmentioning
confidence: 99%